2021
DOI: 10.1007/s10964-021-01492-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Salient Stressors of Adolescence: A Systematic Review and Content Analysis

Abstract: Stressors play a defining role in youth development and, in particular, in adolescent psychological and behavioral adaptation. However, the nature of stressors experienced during adolescence has not been reviewed or investigated comprehensively. To bridge this gap, this investigation conducted a systematic review of adolescent stressors reported in the literature (Study 1, N = 18 studies) and a content analysis of self-reported stressors (Study 2, N = 1,568 adolescents, Mean age = 15.5 years, 41.5% female adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 50 publications
(97 reference statements)
2
26
0
2
Order By: Relevance
“…However, in a previous study on students aged 11–15 years, the mean GHQ score was 11.4 [ 15 ], which is comparable with our results. Negative stressors (e.g., health problems, parental conflicts, peers or friends, romantic problems) and positive stressors (e.g., leisure, school, receiving help, romance, and friendship) are common and intense among adolescents [ 23 ]. In a previous study, adolescent female athletes reported significantly higher self-perceived stress than male athletes [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a previous study on students aged 11–15 years, the mean GHQ score was 11.4 [ 15 ], which is comparable with our results. Negative stressors (e.g., health problems, parental conflicts, peers or friends, romantic problems) and positive stressors (e.g., leisure, school, receiving help, romance, and friendship) are common and intense among adolescents [ 23 ]. In a previous study, adolescent female athletes reported significantly higher self-perceived stress than male athletes [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, adolescent female athletes reported significantly higher self-perceived stress than male athletes [ 4 ]. Stressors play a crucial role in ways that may be deleterious for young people’s psychological and behavioural adaptation to society [ 23 ]. High stress levels have also been reported to be a predictor of sustaining injuries among athletes [ 5 , 24 ], with less recovery and subsequent sport performance [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions framed as stress reduction programs may be more appealing and less stigmatizing to adolescents with psychological needs than mental health interventions targeting for example anxiety or depression. Given that most adolescents experience stressors related to school or social situations at any given moment (Núñez-Regueiro & Núñez-Regueiro, 2021 ), and that they often cope with stress by talking about it (Camara et al, 2017 ), interventions focusing on stress reduction may be perceived by adolescents as a low-threshold and encouraging way to address their psychological needs. The school environment is particularly suitable for such interventions, as adolescents spend a large amount of their time at school (Eccles & Roeser, 2011 ), and the school context is important for adolescents’ emotional, social, and cognitive development (Roeser et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on the onset or end of discrete, potentially stressful life events that occurred within the family or concerned the self. Stressors are conceptualised as common and salient adverse experiences or worries due to the pandemic or related behavioural restrictions that can disrupt the fit between individual and environmental characteristics (Núñez-Regueiro and Núñez-Regueiro, 2021 ). This study focuses on direct pandemic-related health effects and indirect lockdown-related effects, including career-related stressors, social stressors referring to the frequency of social contact, and financial stressors (Graupensperger et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%